ChurchScape : Megachurches and the Iconography of Environment - Bratton, Susan (Book collections on Project MUSE., 2016)
Buildings and landscapes are as much a part of the Christian church as its creeds--reflecting the faith and proclaiming God. The architecture of the church's structures and the curating of its grounds are unique windows into the church's history and the shape of its theological commitments. Birthed in the iconoclastic spirit of the Reformation, the scapes of Protestant churches have experienced massive shifts in design and scope. From humble beginnings--small buildings and cemeteries--churches today can occupy thousands of square feet across hundreds of acres. The modern megachurch, with its extensive campuses, parking lots, and sprawling lawns, has changed how we think about the church and its spaces. Form follows function, and theology is in both. The shifts in scale, style, and symbol within the church's common spaces reflect changes in ecclesial priorities, even as they form the theological imagination in new ways. In ChurchScape, Susan Bratton chronicles the story of the Protestant church's transformation of landscape and building. Citing the influence of college campuses on megachurch architecture, Bratton examines the features that are a part of many megachurch complexes, including waterscapes, iconography, and outdoor art. Taking readers on a cross-country journey to over two hundred churches, Bratton traces the movement from the small parish building of the nineteenth century to the extensive complexes that form today's churchscapes. As she moves from church to church, Bratton describes how all the church's spaces--buildings, greens, gardens, and gateways--together shape its practices, name its beliefs, and form its life together. Bratton's work offers the first historical and theological analysis for the megachurch and its physical planners and planters. She demands that all of us look with new eyes at the ways the church may be an innovator without being disruptive, a place of community without becoming exclusive, and a site of abundance without decadence. The church-in-place must consider how its scapes and spaces reflect its sacred life. - book flap.